Sheep grazing in vineyards benefits wild bees in vineyard embankments and sheep dung attracts dung beetles to vineyards - Felix Fornoff; Johanna Mattenklodt; Frauke Thul; Jörn Buse; Alexandra-Maria Klein; Jakob Hörl; Nicolas Schoof (Basic and Applied Ecology)
Integrated sheep-vineyard systems are an example of ecological intensification. Sheep can replace mulching, thereby reducing the input of fossil fuels and agrochemicals. However, knowledge about the co-benefits of sheep grazing for biodiversity is lacking. This study examined the impact of grazing on wild bee diversity within terraced vineyards and vineyard embankments. Additionally, dung beetle colonization of sheep dung was investigated in the wine-growing region of southwestern Germany. Five vineyards and their terrace risers (embankments) had been grazed by sheep for several years, typically in a rotational system, or were managed conventionally by mulching as control. Wild bee diversity was compared in five pairs of grazed and non-grazed vineyards and five pairs of grazed and non-grazed embankments within one year. Dung beetle diversity, reared from sheep dung collected at three grazed vineyards, was also assessed. In the vineyards, bee abundance and species richness did not differ between grazed plots and mulched controls, but bee abundance increased with flower abundance, and bee species richness increased with flowering herb species richness. In contrast, on vineyard embankments, both species richness and abundance of wild bees were higher on grazed embankments compared to control embankments, whereas flower cover did not have any effect. At least 20 different dung beetle species, including threatened ones, were recorded in sheep droppings of grazed vineyards. This additional food resource may support dung beetle populations, contributing to overall insect biomass, with potential relevance for nature conservation. Our study shows that sheep grazing may support dung beetles, but does not affect bees in vineyards. However, allowing sheep to access vineyard embankments for vegetation management supports wild bees. Therefore, sheep grazing in vineyards offers opportunities for biodiversity conservation and maintaining ecosystem functions, though is not an all-in-one solution.